Differences in Dosage of Red Watermelon Juice to Reduce Blood Pressure in Hypertensive Patients in Ngepungrojo Pati Village - Nabila Fitriana; Sukesih Sukesih; Yulisetyaningrum Yulisetyaningrum (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aimed to determine whether different doses of red watermelon juice, namely 150 ml and 250 ml, were effective in reducing blood pressure among hypertensive patients in Ngepungrojo Village, Pati. It was hypothesized that both doses would lower blood pressure, with a possible difference in effectiveness between the two intervention groups. Research Method: This study used a quasi-experimental design with a pre-test post-test approach involving 32 hypertensive patients selected through total sampling. Respondents were divided into two intervention groups, each receiving 150 ml or 250 ml of red watermelon juice. Blood pressure was measured before and after intervention using a digital sphygmomanometer. Data were analyzed using descriptive statistics, paired sample t-test, and independent sample t-test. Results and Discussion: Both intervention groups showed significant reductions in systolic and diastolic blood pressure after treatment. In the 150 ml group, blood pressure decreased significantly, and similar results were observed in the 250 ml group. However, no statistically significant difference was found between the effectiveness of the 150 ml and 250 ml doses. Implications: Red watermelon juice may be considered a simple non-pharmacological intervention to help control blood pressure in hypertensive patients. Further studies with larger samples and stricter control of confounding factors are recommended.